The Feasibility of a Fast Liver MRI Protocol for Lesion Detection of Adults at 3.0-T - Li, Jing; Ma, Chao; Chen, Yukun; Fu, Caixia; Wang, Xinrui; Kuehn, Bernd; Yang, Qingsong; Lu, Jianping (Frontiers in Oncology, 2021)
Purpose: To investigate the feasibility of a fast liver magnetic resonance imaging (MRI) protocol for lesion detection in adults using 3.0-T MRI. Methods: A fast liver MRI exam protocol was proposed. The protocol included motion-resistant coronal T2-w sequence, axial T2-w fast spin echo sequence with fat suppression, axial in-op phase gradient recalled echo (GRE) T1, axial diffusion weighted imaging (DWI) and axial contrast-enhanced T1 sequences. To evaluate the diagnostic capacity of the proposed protocol, thirty-one consecutive patients (20 males and 11 females; mean age, 53.2 years) underwent a liver MRI exam with conventional sequences, including the proposed protocol as a subset. Images from the conventional protocol and extracted abbreviated protocol were independently read, and the diagnostic concordance rate was assessed for each patient. The concordance analysis is presented as the proportion of concordant cases between the two protocols. Results: The net measurement time of the fast liver MRI protocol without adjustment and waiting time were 4 minutes and 28 seconds. In the 31 patients included in this study, 139 suspicious findings were found from both the conventional liver MR protocol and the fast liver MRI protocol. The diagnostic concordance rate was 96.4%. Conclusions: The fast liver MRI protocol is feasible at 3.0-T, with a shorter exam time and high diagnostic concordance compared to the conventional liver MRI workflow.